Review on Knowledge Sharing: Barriers and Motivations - Ayodele, Freida Ozavize; Liu, Yao; Hasnah, Haron; Sui, Hai Juan (2016)
Knowledge has been perceived as one of the most important resources needed for the survival of any knowledge intensive institution. The dependence of any university on the embedded knowledge of the non-academic staff for impressive benefits requires detail understanding of possible factors that may hamper the dissemination or facilitate the knowledge flow among them. An extensive review on the barriers and motivations influencing knowledge sharing in existing literature was carried out and adapted to the non-academic section of the University. The theoretical findings show that four barrier and motivation factors influence knowledge sharing among the non-academic staff of University. An effective knowledge sharing process among the non-academic section of the University will benefit both the individual non-academic staff and the university at large.